He ain't heavy [videorecording (DVD)] - Smith, David Vincent; George, Leila; Corlett, Sam, 1996-; Scacchi, Greta; Nell, Alexandra (Gravitas Ventures, 2025)
Jade has sacrificed the better part of her life to rescue her little brother Max from drug addiction. In desperation, Jade locks him inside a vacant rural home in an attempt to get him clean. Before long, a shocking discovery is made.